IMPLEMENTATION OF STRATEGIC MANAGEMENT IN IMPROVING STUDENT LEARNING MOTIVATION IN ISLAMIC UNIVERSITIES - M. Agus Kurniawan; Suci Hartati (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2025)
This research investigates strategic management implementation in enhancing student learning motivation within Islamic higher education institutions through a phenomenological qualitative approach. An in-depth study explores motivation enhancement complexity by identifying three critical dimensions: structural, pedagogical, and spiritual. Research findings reveal that institutional transformation toward flexible and participatory models, student-centered learning method innovations, and systematic Islamic value internalization significantly influence learning motivation dynamics. Key success factors include transformative leadership, comprehensive mentoring systems, continuous faculty capacity development, and supportive technological infrastructure. The resulting strategic management model offers an integrative framework synergizing academic, spiritual, and managerial aspects within the Islamic higher education context, providing a holistic approach to stimulating student learning motivation